2020
DOI: 10.3748/wjg.v26.i9.960
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of atypical hepatic hemangioma from liver metastases: Diagnostic performance of a novel type of color contrast enhanced ultrasound

Abstract: conceived and designed the study, performed the examinations, and the data analysis; Sun Y performed the pathologic analysis. Wu XF and Bai XM contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…The diagnostic accuracy of MRI with liver-specific contrast agents is significantly higher than that of CEUS [ 9 ]. Wu et al reported an association between RE representing hepatic uptake of Gd-EOB-DTPA and the METAVIR scoring system used to differentiate normal liver parenchyma from higher stages of hepatic fibrosis [ 10 ]. Bai et al demonstrate that high intensity on DWI, coupled with high signal intensity on T2, is the most specific feature to distinguish atypical HCC from dysplastic nodules (sensitivity 80.0%, specificity 100%, positive predictive value 100%, and negative predictive value 78.3%).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The diagnostic accuracy of MRI with liver-specific contrast agents is significantly higher than that of CEUS [ 9 ]. Wu et al reported an association between RE representing hepatic uptake of Gd-EOB-DTPA and the METAVIR scoring system used to differentiate normal liver parenchyma from higher stages of hepatic fibrosis [ 10 ]. Bai et al demonstrate that high intensity on DWI, coupled with high signal intensity on T2, is the most specific feature to distinguish atypical HCC from dysplastic nodules (sensitivity 80.0%, specificity 100%, positive predictive value 100%, and negative predictive value 78.3%).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The contrast agents washed out very rapidly during the portal phase and presented hypo-enhancement until the end of the late phase. Wu et al [ 28 ] showed that metastatic lesion presented non-enhancement during the late phase. Zhang et al [ 29 ] found that lung primary lesion’s MLC showed no significant enhancement in CEUS, which was contrary to other findings.…”
Section: Discussionmentioning
confidence: 99%
“…Yang (15) once succeeded in diagnosing a case of thyroid haemangioma with CEUS preoperatively, and believed that the "slow in and slow out" pattern of contrast filling and perfusion was the characteristic feature of haemangioma. Wu (16) summarized the typical features of liver haemangioma as peripheral nodular and centripetal enhancement during the arterial phase followed by hyperor isoenhancement during the portal venous and late phases on CEUS. MRI, especially enhanced MRI can also provide valuable diagnostic information for haemangioma before surgery (1)(2)(3)17).…”
Section: Discussionmentioning
confidence: 99%